Inhibition of GSK3 by lithium, from single molecules to signaling networks - Freland, Laure; Beaulieu, Jean-Martin (Frontiers in Molecular Neuroscience, 2012)
For more than 60 years, the mood stabilizer lithium has been used alone or in combination for the treatment of bipolar disorder, schizophrenia, depression and other mental illnesses. Despite this long history, the molecular mechanisms trough which lithium regulates behavior are still poorly understood. Among several targets, lithium has been shown to directly inhibit glycogen synthase kinase 3 alpha and beta (GSK3α and GSK3β). However in vivo, lithium also inhibits GSK3 by regulating the activity of other mechanisms like the formation of a signaling complex comprised of beta-arrestin 2 and Akt. Here, we provide an overview of in vivo evidence supporting a role for inhibition of GSK3 in some behavioral effects of lithium. We also explore how regulation of GSK3 by lithium within a signaling network involving several molecular targets and cell surface receptors (e.g. G protein coupled receptors and receptor tyrosine kinases) may provide cues to its relative pharmacological selectivity and its effects on disease mechanisms. A better understanding of these intricate actions of lithium at a systems level may allow the rational development of better mood stabilizer drugs with enhanced selectivity, efficacy and lesser side effects.